Quantiles of growth: Household debt and growth vulnerabilities in Finland - Juho Nyholm; Ville Voutilainen (Bank of Finland, 2021)
We analyze the relationship of the distribution of future GDP growth and accumulation of household debt in Finnish macroeconomic data from 1980 to 2019. We find clear evidence that exuberant accumulation of household debt is related to the thickening of the left tail of the future growth distribution, while reaction in the right tail of the distribution is more damped. Thus, there is a link between rapid household debt growth and increase in probabilities of more severe downturns. We also re-establish the result of Mian, Sufi, and Verner (2017) that, on average, rapid household debt accumulation is associated with slower subsequent economic growth. While the relationship of the debt growth and negative tail effects is robust along our sample period, the association between debt growth and median of the GDP growth distribution varies from significantly negative to zero, depending on the estimation sample and especially if the Finnish Great Depression of early 1990's is included.
urn:nbn:fi:bof-202105271262
Keywords: E44; E47; G51; 330; household debt; GDP forecasting; quantile regression